Popular Sentiments and Political Failures: Understanding the Disintegration of the Republic of Moldova, 1989–1990 - Solonari Vladimir (Comparative Southeast European Studies)
This article revisits the foundational years of 1989–1992 when the Republic of Moldova obtained its independence and simultaneously suffered territorial losses due to separatist movements. The quasi-official view in today’s Moldova holds that separatist movements of that era in Transnistria and Gagauzia were the results of Moscow’s meddling in Moldovan affairs aimed at punishing the Moldovans’ quest for independence. The paper argues that this interpretation attributes too much power to the decision-makers in Moscow, and also strips local actors of agency. Instead, the article calls for a renewed focus on the developments in Moldova itself and for discourses developed by separatist leaders and opinion-setters to be treated as representative of genuine popular sentiment. It argues that the Moldovan national movement alienated the non-Moldovan population whose primary means of communication was Russian. The article relies on personal recollections as well as numerous published primary and secondary sources.